Płeć emigracji. Kobiece i męskie wzorce emigrowania = The gender of emigration. Female and male styles of emigrating - Pawlak, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The subject of analysis presented in this article are similarities and differences in female and male styles of emigrating. The analysis is based on the subject literature and own researches of the author (open interviews) among migrants and their families, carried out in the years 2010-2014. Female and male patterns of migration differ significantly when it comes to taking up employment on emigration and integrating with host communities.
Keywords: migracja zarobkowa; emigracja wahadłowa; styl migracji; koszt migracji; migracja kobiet; migracja mężczyzn; economic migration; circular emigration; styles of migration; costs of migration; female migration; male migration